Mechanical & physical properties of hybrid cross laminated timber (HCLT) fabricated using solid wood & plywood - Mansoor, Noorsyazwani (2019)
Hybrid cross laminated timber (CLT) using the structural composite lumber (SCL) were developed in this study using Dark Red Meranti (solid timber) and plywood. The usage of plywood as cross and outer layers of hybrid CT was done to improve the mechanical and physical properties of the generic CLT. The objective of this study was to evaluate the mechanical and physical properties of HCLT fabricated with the combination of local species of lumber and plywood. Three samples of CLT with different configurations of layup were prepared with the same size dimension. These samples were then cut into dimension according to the BS EN408 standard for mechanical testing and BS EN391 standard for physical testing. As for the mechanical testing, 4-point bending tests were conducted and MOE & MOR values of the tested samples were determined. The delamination test was conducted to obtain the percentage of total and maximum delamination of the HCLT boards. It was found that the highest value of MOE and MOR was obtained from samples fabricated using solid wood. The property of HCLT using plywood material as outer layer has depicted a slight reduction of MOE and MOR values. The percentage of total and maximum delamination is lower when the outer layer of CLT was replaced by the plywood.